Management as a necessary tool for the prevention of violence against women - Favier, Meglis Rivero; Manzanares, Nayra Martínez; Loor, Karla Mercedes Mendoza; Zambrano, Telly Yarita Macías (International research journal of management, IT and social sciences, 2021)
The chair "Women, family and Guantanamo society" in the Guantánamo province as part of its functions intends the following investigation that addresses the theme of the prevention of violence against women from its management. This has the purpose of contributing to the educational preparation of agencies and social agents as an effective response to the demands of today's Cuban society. The study assumes the methodological-materialist and historical dialectical conception with the use of general research methods, with references, aspects of historical and theoretical-methodological evolution in the sociological, psychological, pedagogical and legal areas. The diagnostic results of the study made it possible to design as a methodological proposal a management strategy for the prevention of violence against women, which is strengthened from the integration of agencies and social agents, which places the University as the most important educational agency of the community.